2012
DOI: 10.3402/mehd.v23i0.18579
|View full text |Cite
|
Sign up to set email alerts
|

Defining microbiota for developing new probiotics

Abstract: The human body harbors complex communities of microbes that play a prominent role in human health. Detailed characterization of the microbiota in the target population forms the basis of probiotic use. Probiotics are defined as live bacterial preparations with clinically documented health effects in humans, and independent of their genus and species, probiotic strains are unique and their beneficial properties on human health have to be assessed in a case-by-case manner. Understanding the mechanisms by which p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 49 publications
0
11
0
Order By: Relevance
“…In this context, previous studies reported associations between Chlamydophila pneumoniae [ 124 ] as well as herpes simplex virus infection and AD [ 125 ]. The possible mechanisms that link microbiota to AD include (1) interactions between the gut microbiota and the CNS in a “microbiota-gut-brain axis” [ 123 ], which modify immune response, enhancing response to cerebral A β [ 126 ], (2) microbiota that could promote prion-like behavior of amyloid proteins leading to neurodegeneration [ 127 ], and (3) microbiota changes during aging such as the increase in the proportion of Bacteroidetes to Firmicutes as well as the reduction of bifidobacterial counts [ 128 ], which decrease the synthesis of proinflammatory cytokines [ 129 ]. Finally, epidemiological links between oral bacteria and AD have been reported [ 121 ], due to the increase of TNF- α production [ 130 ].…”
Section: Pathogenesis and Clinical Features In Admentioning
confidence: 99%
“…In this context, previous studies reported associations between Chlamydophila pneumoniae [ 124 ] as well as herpes simplex virus infection and AD [ 125 ]. The possible mechanisms that link microbiota to AD include (1) interactions between the gut microbiota and the CNS in a “microbiota-gut-brain axis” [ 123 ], which modify immune response, enhancing response to cerebral A β [ 126 ], (2) microbiota that could promote prion-like behavior of amyloid proteins leading to neurodegeneration [ 127 ], and (3) microbiota changes during aging such as the increase in the proportion of Bacteroidetes to Firmicutes as well as the reduction of bifidobacterial counts [ 128 ], which decrease the synthesis of proinflammatory cytokines [ 129 ]. Finally, epidemiological links between oral bacteria and AD have been reported [ 121 ], due to the increase of TNF- α production [ 130 ].…”
Section: Pathogenesis and Clinical Features In Admentioning
confidence: 99%
“…The human gastrointestinal tract (GIT) is inhabited by a complex and dynamic population of around 500–1000 different microbial species 1 . HM exhibits large variation among individuals in relation to internal and external factors such as genetic factors, age, diet, and health, and remains in a complex equilibrium 2 . Although the exact composition of the microbiota is not known, advances in genomic technologies have recently begun to unravel our microbial partners 3 …”
mentioning
confidence: 99%
“…Microbiota development of the infant is rapid and depends on the first inoculum, the mother’s microbiota, mode of delivery, type of feeding, and the environment, including weaning food practices and the use of antimicrobials. 2 , 6 *…”
mentioning
confidence: 99%
“…Balancing the composition of these microbes in gastrointestinal tract is handy not only in promoting effective digestion and maximum gain of nutrients, but also important in increasing the capacity of host in excluding danger microorganism and hence contributes in preventing diseases [1]. Lactobacilli are known to be common inhabitant of animal intestinal microflora and many reports have suggested them to provoke various positive health attributes.…”
Section: Introductionmentioning
confidence: 99%